ANALISIS KERUSAKAN POHON DI JALAN AHMAD YANI KOTA PONTIANAK - Stalin, Marsi; Diba, Farah; HusniANALISIS KERUSAKAN POHON DI JALAN AHMAD YANI KOTA PONTIANAK (Tree damage analysis on, Harnani (Universitas Tanjungpura, 2013)
Trees as part of the green open space (GOS) has a very important function. Trees can lose its function, even the presence of trees can cause economic loss if the trees condition is worst untreated trees and fallen into the road. Moreover, the ecological functions will not work well. This study aimed to obtain data on the extent of damage that occurs in the trees on Ahmad Yani street Pontianak. The benefit of this research is to provide important information about the damage of the trees then it can be used as a reference for the proper trees care activities. The experiment was conducted using the Forest Health Monitoring (FHM), which is monitoring forest stand conditions to analyze the present and the future, and provide recommendations for improvement management. The method included to identify the species orgenus, height and diameter of the tree which is then followed by examining the type of damage that occurs in the tree. Type of tree damage on Jalan Ahmad Yani Pontianak city as much as 6 types encountered. Types of damage include: a) cancer, b) konk or decayed further, c) open wound, d) broken or dead branches, e) excessive branching or brum and f) the leaves change color. The most prevalent types are further decomposed konk or 47.5% of the total cases were found, while the least damage is the damage type of the cancer by 1.66%. Conditions trees on Jalan Ahmad Yani Pontianak City considered healthy by Level Damage Index (LIK) of 0.37. Trees are recorded as many as 110 trees and total tree damaged was 15.78% of the total number of trees was observed (697 tree), meanwhile 97.27% considered healthy and slightly damaged was 2.72%. Keywords : tree damage, forest health monitoring, level damage, Pontianak city